Do High-Speed Rails Improve the Allocation Level of Medical Resources? - Wu, Hong; Rong, Xingbo; Zhao, Mengfan (Frontiers in Sustainable Cities, 2022)
Transportation is an important factor that affects social public health and basic services. The opening of high-speed rails also has an impact on the country's urban medical and other basic health services. Based on the panel data of 280 cities at the prefecture level and above in China from 2008 to 2018, this study uses a multi-period difference-in-difference model to explore the impact of opening high-speed rails on the level of urban medical resources, and uses the mediation effect model to analyse its path of influence. The empirical results show that opening high-speed rails has significantly increased the level of medical resources in the city, and the impact has a time lag of about three years. Second, government actions are one of the mechanisms by which the opening of high-speed rails affect the level of medical resources. Finally, there is regional heterogeneity in the impact of high-speed rails opening on medical resources. The opening of high-speed rails has a stronger role in promoting the level of medical resources in eastern cities and provincial capitals. The conclusion of the article has certain policy significance for improving the social and economic welfare of HSR and promoting the rational allocation of medical resources.